Serum club cell protein 16 is associated with asymptomatic airway responsiveness in adults: Findings from the French epidemiological study on the genetics and environment of asthma. Issue 8 (11th August 2015) - Rava, Marta; Le Moual, Nicole; Dumont, Xavier; Guerra, Stefano; Siroux, Valerie; Jacquemin, Benedicte; Kauffmann, Francine; Bernard, Alfred; Nadif, Rachel
Abstract Background and objective Club cell secretory protein (CC‐16) is a sensitive biomarker of airways epithelium integrity. It has gained interest as a biological marker in chronic lung diseases because of its presumed relationship to inflammation. Little is known about the association between CC‐16 serum level and asthma, lung function and airway responsiveness (AR). Methods Serum CC‐16 level was determined by latex immunoassay in 1298 participants from the French Epidemiological case‐control and family‐based study on Genetics and Environment of Asthma (EGEA) (mean age 43 years; 49% men, 38% with asthma). Pre‐bronchodilator lung function (forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC) and FEV1/FVC) and degree of AR, expressed as a function of the dose–response slope to methacholine test were measured. Standardized residuals CC‐16 z‐scores were obtained by regressing CC‐16 level on the glomerular filtration rate. CC‐16 z‐scores were correlated with asthma, lung function and AR in participants with and without asthma. Results CC‐16 geometric mean level was 12.4 μg/L (range: 2.2–70.6 μg/L). In participants without asthma, lower CC‐16 z‐scores was associated with impaired FEV1/FVC% (β = 0.50 (95% CI: 0.06, 0.95) and with higher degree of AR (β = 0.24 (95% CI: 0.09, 0.39)). CC‐16 was not associated with impaired lung function or AR in participants with asthma. Conclusions Lower CC‐16 serum level was associated with impaired lung function and AR, suggesting that serum CC‐16 level may reflect early damages to the lung epithelium in adults without asthma.